2006
DOI: 10.1111/j.1939-1676.2006.tb02910.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Signs, Magnetic Resonance Imaging Features, and Outcome After Surgical and Medical Treatment of Otogenic Intracranial Infection in 11 Cats and 4 Dogs

Abstract: Brainstem dysfunction resulting from central extension of infection is a life-threatening complication of otitis media/interna (OMI) that has been described infrequently in dogs and cats. We review the clinical signs of disease, diagnostic findings, and results of surgical and medical treatments of brainstem disease attributable to otogenic intracranial infection in cats and dogs. Eleven cats and 4 dogs were examined because of acute, subacute, or chronic clinical signs of brain disease including central vesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 49 publications
5
77
1
Order By: Relevance
“…Reviewers were then asked to specify the most likely brain disease represented by the MR abnormalities. Reviewers were permitted to diagnose inflammatory lesions as granulomatous meningoencephalitis (GME), 21 necrotizing encephalitis (NE), 8 bacterial encephalitis, 22 canine distemper virus encephalitis, 23 Neospora caninum, 24 fungal encephalitis, 25,26 or other/unknown. Neoplastic lesions could be classified by reviewers as meningioma, 5 glioma (oligodendroglial, astrocytic, or mixed-glial origin), 7 choroid plexus tumor (papilloma or carcinoma), 27,28 ependymoma, 29 histiocytic sarcoma, 30 lymphoma, 4 hemangiosarcoma, 31 pituitary tumor, 3 metastatic neoplasia, 4,20 or other/unknown.…”
Section: Image Analysismentioning
confidence: 99%
“…Reviewers were then asked to specify the most likely brain disease represented by the MR abnormalities. Reviewers were permitted to diagnose inflammatory lesions as granulomatous meningoencephalitis (GME), 21 necrotizing encephalitis (NE), 8 bacterial encephalitis, 22 canine distemper virus encephalitis, 23 Neospora caninum, 24 fungal encephalitis, 25,26 or other/unknown. Neoplastic lesions could be classified by reviewers as meningioma, 5 glioma (oligodendroglial, astrocytic, or mixed-glial origin), 7 choroid plexus tumor (papilloma or carcinoma), 27,28 ependymoma, 29 histiocytic sarcoma, 30 lymphoma, 4 hemangiosarcoma, 31 pituitary tumor, 3 metastatic neoplasia, 4,20 or other/unknown.…”
Section: Image Analysismentioning
confidence: 99%
“…The only curative treatment for canine cholesteatoma reported to date is surgery with total ear canal ablationlateral bulla osteotomy (TECA-LBO) and ventral bulla osteotomy. 1,2,10,16 The prime objective of surgery for cholesteatoma is to remove all keratinous debris and stratified squamous epithelium; 17 recurrence postsurgery is common in animals. [1][2][3] To the best of the authors' knowledge, 15 reports (covering a total of 70 cases) of canine cholesteatoma have been published.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] To the best of the authors' knowledge, 15 reports (covering a total of 70 cases) of canine cholesteatoma have been published. [1][2][3][4][5][6][7][8]10,13,15,16,[18][19][20] Reports in which the diagnosis of cholesteatoma was confirmed by histopathological evaluation in combination with CT and MR imaging are limited. 1,8 No clinical studies of nonsurgical management for aural cholesteatoma have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…There is a limited number of reports on the usefulness of MRI in the diagnosis of feline ear diseases (Allgoewer et al 2000;Mellema et al 2002;Garosi et al 2003;Sturges et al 2006). The otitis of the middle ear is usually problematic for diagnosis (Allgoewer et al 2000).…”
Section: Discussionmentioning
confidence: 99%